Impact of multi-crop planter business on service providers’ livelihood improvement in some selected areas of Bangladesh (Bangladesh Journal of Agricultural Research, 2019)
The custom hiring of the Versatile Multi-crop Planter (VMP) is a profitable enterprise for Local Service Providers (LSP) that could improve their household livelihood but the impacts have not yet been assessed in Bangladesh. In this study, we assessed the use pattern and profitability of custom-hiring the VMP, and its impacts on LSPs’ livelihood. A total of 18 LSP were purposively selected from Rajshahi, Thakurgaon, Mymensingh, and Rajbari districts for this study. The study revealed that LSPs effectively utilized VMP and 2-wheel tractor (2WT) for 4-6 months. They earned Tk. 1,42,434 (with incentive on VMP) and Tk. 1,36,134 (without incentive) per year as net income. The average payback periods were 0.72 and 0.98 years with and without incentive, respectively. The annual break-even of a VMP use was 7.79 ha. The LSPs reported a considerable cash (annual income increased by 34.9 %), and capital enhancement, e.g., land holdings (8.3 %), value of livestock (11.2 %), dwelling houses (36.6 %), household furniture (19 %), and modern amenities (45.5 %). The increased incomes from VMP custom hiring were mostly spent on nutritious food, land mortgage-in, and dwellings. The LSPs reported minor challenges such as being unable to use this machine in the wetland condition (61 %), no seating arrangement on the machine during operation in small plots (56 %), long time taken to complete sowing due to narrow planting width per pass (50 %), farmers’ skepticism about the planting machine as it is still new technology (44 %), and lack of skilled drivers (17 %). Financial support and technical assistance should be made available by the government for LSPs and local manufacturers to accelerate greater adoption of the VMP.Bangladesh J. Agril. Res. 44(3): 409-426, September 2019